2014
DOI: 10.1080/21568316.2014.890129
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Community Leadership in Rural Regions: Linking Mobility, Entrepreneurship, Tourism Development and Community Well-Being

Abstract: This study addressed contradictions in the tourism development literature about the importance of locals versus outsiders and the role of entrepreneurs. More specifically, it explored the characteristics of tourism entrepreneurs and their connections to the destination community, their roles as community leaders and the overall outcomes of tourism development for the host community. This exploration was conducted through a qualitative analysis of 47 case studies of rural tourism development and used concepts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 53 publications
2
44
0
6
Order By: Relevance
“…This is in accordance with Zhang (2013), who acknowledges that studies that link tourism and wellbeing are not the norm. (Filep, 2014b); (Jenkins & Romanos, 2014); (Kruger, Saayman, & Ellis, 2014); (Lee, Kruger, Whang, Uysal, & Sirgy, 2014); (Moscardo, 2014). Coghlan, 2015); (Kim, Lee, Uysal, Kim, & Ahn, 2015); (Mnguni & Giampiccoli, 2015); (Morgan, Pritchard, & Sedgley, 2015); (Tuohino & Honkanen, 2015); (Willis, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with Zhang (2013), who acknowledges that studies that link tourism and wellbeing are not the norm. (Filep, 2014b); (Jenkins & Romanos, 2014); (Kruger, Saayman, & Ellis, 2014); (Lee, Kruger, Whang, Uysal, & Sirgy, 2014); (Moscardo, 2014). Coghlan, 2015); (Kim, Lee, Uysal, Kim, & Ahn, 2015); (Mnguni & Giampiccoli, 2015); (Morgan, Pritchard, & Sedgley, 2015); (Tuohino & Honkanen, 2015); (Willis, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The review of Hartwell et al (2016) reflected that this new conceptualization can be a novel way to promote destinations using wellbeing as a marketing tool. Moscardo (2014) found that the community entrepreneurs showed higher success in promoting positive outcomes for tourism and for locals. Additionally, they concluded that financial and built/physical capital were less important than social and human resources for the development of the community and that administration structures are fundamental for the sustainability of tourism development.…”
Section: Reference Location Paper Aim(s)mentioning
confidence: 99%
“…In addition, local communities require leaders to take the initiative to achieve success in tourism development [65]. Thus, entrepreneurship is a very important character of community leaders who lead other residents to promote rural tourism development [63,105]. Pre-existing experiences are also important for community leaders.…”
Section: Community Leadership In Rural Tourismmentioning
confidence: 99%
“…The knowledge transfer and repository aspects of this research are secondary objectives but by no means of lesser importance (Moscardo, 2014;Arnaboldi & Spiller, 2011;Geuna & Muscio, 2009;Agrawal, 2001;Raivola et al, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A further focus is skills acquisition to manage new knowledge and extract maximum shared benefit with new social capital held in trust for future generations (Raivola et al, 2001;Moscardo, 2014;Shone et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%